Outcome of Dengue Patients Admitted in the PICU of Bangladesh Shishu Hospital & Institute - Akhter, Rowshan Jahan; Paul, Shubhra Prakash; Ahmed, Farid (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Recent re-emergence of dengue patient among Bangladeshi children have created a huge burden in the morbidity and mortality of our children. Objectives: This study was designed to document the outcome of dengue patients, admitted in the ICU of Bangladesh Shishu Hospital & Institute (BSH&I). Methods: This retrospective observational study was performed among the children having dengue infection and who were admitted in the PICU of BSH&I from 1st June 2019 to 31st December 2019. All patients who were diagnosed as dengue fever by serological tests (NS1, Dengue IgG & IgM) and those who were admitted in the PICU were included in this study. Total one hundred and twenty-six patients were enrolled. Data were collected from hospital record of the Dengue patients. Results: Mean age of the Dengue patients were 5.91(±3.53) years. Most of the patients suffering from dengue fever were urban dwellers; among them 52.4% were female. Presenting symptoms during admission in the PICU were fever which was present in 119 patients (94.4%), followed by hypotension in 106 (84.1%) patients. Severe dengue (SD) was diagnosed in maximum number of cases (i.e., 62.7%), followed by Dengue fever with warning signs (DFWS) in (20.6%) and Expanded Dengue Syndrome (EDS) in 16.7%. Maximum cases received crystalloid (98.4%), about 51.6% patients received colloid. A good number of patients received blood transfusion (23%), plasma was received in (23%) and albumin was received in (33.3%) cases. Majority of the patients received Oxygen (80.2%); antibiotics were prescribed in 87.3% cases. Fifty-five percent patients received inotropes for the management of shock. The overall outcome revealed 75.4% patients were cured and discharged. Only 21.43% patients died in the PICU despite protocol-based management. Death due to severe dengue was 15(18.9%) out of 79, followed by death due to Dengue Hemorrhagic fever with warning signs which was 8 (30.7%) out of 26 and death in Expanded Dengue syndrome was 4(19.04%) out of 21. Conclusion: This retrospective study found that majority of the Dengue patients admitted in PICU has survived. However the death due to Dengue with warning signs was higher than death in severe Dengue cases. Delayed recognition of warning signs along with delayed referral to PICU may be responsible for such outcome. DS (Child) H J 2021; 37(2): 103-108